Given:
Ethan is 23 years older than Evan
So, let Ethan is (x) years old
And Evan is (y) years old
So, the difference between them is 23 years old
so, x - y = 23
And the sum of Ethan and Evan's age is 43
so, x + y = 43
So, we have the following system of equations:
![\begin{gathered} x-y=23 \\ x+y=43 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e8bwvlij5vvgy5un90o8heqd7zjgwmkmuo.png)
add the equations to eliminate (y):
![\begin{gathered} (x-y)+(x+y)=23+43 \\ 2x=66 \\ x=(66)/(2)=33 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j8kdvgi0th9j2w4v4uvrirajqf71n5wrcz.png)
Now, substitute with (x) into the second equation to find (y):
![\begin{gathered} 33+y=43 \\ y=43-33=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mo3rzzqj7nm0lox486t3tg0yhh18lr0zad.png)
So, the answer will be:
Ethan's age = x = 33
Evan's age = y = 10